An efficient sorbent based on CuCl2 loaded CeO2-ZrO2 for elemental mercury removal from chlorine-free flue gas. (15th March 2018) - Zhou, Zijian; Liu, Xiaowei; Hu, Yingchao; Liao, Zhiqiang; Cheng, Shan; Xu, Minghou
Abstract: To remove elemental mercury (Hg 0 ) in chlorine-free coal combustion flue gas efficiently, CuCl2 loaded CeO2 -ZrO2 sorbents (denoted as CC/CZ) were developed. In this way, the abundant Cl and affluent active chemical adsorbed oxygen (O∗) on the surface of the sorbent would be combined and made full use for Hg 0 removal. XRD, XPS, SEM, Raman, TG, and N2 adsorption/desorption were employed to characterize the sorbents. Hg 0 removal behaviors over CC/CZ were studied using a lab-scale fixed-bed reactor. The sorbent with optimal loading 6% CuCl2 exhibited superior and stable performances (89.6–97.1%) within a much wider applicable temperature range (100–300 °C) in the absence of HCl. The results also indicated that 6%CC/CZ exhibit very good performance at lower temperature (100–200 °C). The interaction between Cl and chemical adsorbed oxygen was observed and probably responsible for its superior Hg 0 removal performance. XPS results of the fresh, thermal-treated, and spent 6% CuCl2 /CZ may explain the Hg 0 oxidation process. Hg 0 was mainly oxidized by the generated active chlorine species and the main reaction product was HgCl2 . The active chlorine species were formed due to the interaction between chlorine and chemical adsorbed oxygen species.